Instant Efficient Pollution Abatement under Non-Linear Taxation and Asymmetric Information: The Differential Tax Revisited - Paul Mensink (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper analyzes incentives for polluting firms to exchange abatement cost information under the non-linear pollution tax scheme (differential tax') introduced by Kim and Chang [J. Regul. Econom. 5, 1993, 193-197]. It shows that polluting firms have - under mild conditions - an incentive to join a coalition whose members mutually truthfully exchange information as well as commit themselves with respect to their abatement decisions. As a result, the differential tax triggers instantly - i.e. no abatement adaptation is needed efficient abatement levels without the regulator knowing marginal abatement costs. Consequently, this paper shows that differential taxation results in lower social costs than traditional non-linear taxation which triggers efficient emissions only after a period of non-efficient abatement.
Keywords: C71; D62; D82; Q20; 330; Externalities; Pollution taxes; Coalition formation; Non-linear taxation; Asymmetric information; Co-operative game theory; Umweltschutz; Ökosteuer; Koalition; Steuertarif; Asymmetrische Information; Theorie